2021
DOI: 10.3390/ijerph18073427
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Risk, Self-Efficacy and Social Trust during the Diffusion of Covid-19 in Italy

Abstract: The Coronavirus pandemic has affected the lives of people all over the world. The perception of risk and people’s consequent behaviour during a pandemic are very complex and are affected by multiple cultural and psychological factors. The aim of this study was to investigate the change in risk perception, perceived self-efficacy and the perceived trust in the behaviour of others, the decisions of health authorities and government provisions, as well as the variation of self-restraint behaviours during the spre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 43 publications
2
35
0
Order By: Relevance
“…As already pointed out by Dresel et al (2015), resources management strategies, i.e., the ability to manage external resources, are just as important as internal emotional control., as in seeking for help, or organizing one's workplace, as well as to managing and regulating internal resources, such as effort regulation, time management, attentional regulation, and motivation. In the university context of the last two years, the transition from face-to-face to remote teaching, as a result of the limitations of the covid-19 pandemic, has strongly emphasized the need for students to possess pronounced selfmanagement skills in their learning processes in order not to fall behind on scheduled paths and deadlines and also to maintain a good level of perceived psychological well-being (Pelikan et al, 2021;Diotaiuti et al, 2021a). It has been observed in several studies how distractions at home and reduced social interaction with other students and faculty can negatively affect study time management and adaptation to the new emergency condition that requires students to have a higher level of autonomy and metacognitive control (Rasheed et al, 2020;Tezer, 2020;Alyami et al, 2021;Biwer et al, 2021;Diotaiuti et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…As already pointed out by Dresel et al (2015), resources management strategies, i.e., the ability to manage external resources, are just as important as internal emotional control., as in seeking for help, or organizing one's workplace, as well as to managing and regulating internal resources, such as effort regulation, time management, attentional regulation, and motivation. In the university context of the last two years, the transition from face-to-face to remote teaching, as a result of the limitations of the covid-19 pandemic, has strongly emphasized the need for students to possess pronounced selfmanagement skills in their learning processes in order not to fall behind on scheduled paths and deadlines and also to maintain a good level of perceived psychological well-being (Pelikan et al, 2021;Diotaiuti et al, 2021a). It has been observed in several studies how distractions at home and reduced social interaction with other students and faculty can negatively affect study time management and adaptation to the new emergency condition that requires students to have a higher level of autonomy and metacognitive control (Rasheed et al, 2020;Tezer, 2020;Alyami et al, 2021;Biwer et al, 2021;Diotaiuti et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…The fifth factor measures perceived self-efficacy in an emergency situation (i.e., feeling able to face unexpected events, relying on one's own abilities in emergencies, being able to remain calm in facing difficulties). This is a very delicate aspect in the evaluation of emergency response because the occurrence of threat and damage significantly affects the psycho-physical balance of the person and interferes with the ability to feel able to face difficulties (Weber and Schulenberg, 2019 ; Diotaiuti et al, 2021b ). Self-efficacy has been associated in several studies with improved behavioral response and recovery in the face of various threats and traumas (Tang and Wong, 2003 ; Benight et al, 2008 ; Cieslak et al, 2008 , 2009 ; Hirschel and Schulenberg, 2009 ; Bults et al, 2011 ; Williams et al, 2015 ; Adams et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this scheme it is possible to identify an opportunity for the growth of the person, who does not stiffen by withdrawing in his anxieties, but externalizes attention with prosocial and network initiatives (Yue and Yang, 2021 ). Adaptive and supportive modes could contribute significantly to nourish the person's sense of self-efficacy and limit personal vulnerability to stress (see Saccinto et al, 2013 ; Diotaiuti et al, 2021b ). Recently, in their study Hou et al ( 2020 ) stressed the protective role of self-efficacy in limiting the symptoms of post-traumatic stress disorder and the perception of fatigue in health care workers.…”
Section: Introductionmentioning
confidence: 99%
“…These findings support the notion that pandemic-related cognitions affect the different appraisal of social scenarios. The increased motivation for and implementation of protective measures due to a heightened perceived risk of infection with SARS-CoV-2 (13, 17) possibly lead to a higher valence of lower risk social situations that are more in line with personal self-restraint intentions (14). It might thus be the case that lower risk situations were more appreciated during the first wave of the pandemic because they give a sense of safety.…”
Section: Social Factors (M1)mentioning
confidence: 99%
“…Several studies found that the perceived risk of getting infected with SARS-CoV-2 increased with the implementation of protective measures and public health messages (13,14) and is associated with experience with the virus as well as local occurrences of SARS-CoV-2-infections (15,16). A higher risk perception is associated with more protective behavior such as social distancing and hand washing (13,17) and might in turn lead to a devaluation of social situations with an increased risk of infection.…”
Section: Introductionmentioning
confidence: 99%